2003
DOI: 10.1002/adfm.200304261
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Ion Etching of Cylindrical Polyferrocenylsilane Block Copolymer Micelles: Fabrication of Ceramic Nanolines on Semiconducting Substrates

Abstract: The diblock copolymers, poly(isoprene‐block‐ferrocenyldimethylsilane) (PI‐b‐PFDMS) and poly(ferrocenyldimethylsilane‐block‐dimethylsiloxane) (PFDMS‐b‐PDMS), form cylindrical micelles with an organometallic polyferrocenylsilane core in a solvent of hexanes. These cylindrical micelles were deposited onto a Si substrate from solution by either spin or dip coating, and upon reactive ion etching, continuous ceramic nanolines with lengths of micrometers and widths as small as 8 nm were created. The nanolines were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 31 publications
0
78
0
Order By: Relevance
“…graphy due to the etch resistance of the PFS block. [10,17,[44][45][46] To investigate whether PFG block copolymers can also function as nanolithographic templates, thin films of 6 and 7 were prepared by spin-coating onto silicon wafers and subsequently exposed to an Ar plasma. AFM height images of the etched films ( Figure 7) showed that after exposure to the plasma, the organic phase (PI) has been almost exclusively removed.…”
Section: Thin Films Of Pi-b-pfdmg Diblock Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…graphy due to the etch resistance of the PFS block. [10,17,[44][45][46] To investigate whether PFG block copolymers can also function as nanolithographic templates, thin films of 6 and 7 were prepared by spin-coating onto silicon wafers and subsequently exposed to an Ar plasma. AFM height images of the etched films ( Figure 7) showed that after exposure to the plasma, the organic phase (PI) has been almost exclusively removed.…”
Section: Thin Films Of Pi-b-pfdmg Diblock Copolymersmentioning
confidence: 99%
“…[17] Moreover, shell-cross-linked cylindrical PI-b-PFS block copolymer micelles can act as hosts for onedimensional arrays of metal and semiconductor metal generating peapod-type nanostructures by in situ redox reactions between the PFS core and metal ions. [18] Recently, it has been discovered that short cylindrical micelles generated by ultrasonication can undergo crystallizationdriven living polymerization to form block co-micelles upon addition of further block copolymer.…”
mentioning
confidence: 99%
“…In recent years, nanoscale metallic features directly interfacing to semiconductors is a new area of nanoscience and nanotechnology. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, reports on synthesis of materials other than metals are scarce. [18][19][20] Prussian Blue (PB), formula Fe III4 (Fe II (CN) 6 ) 3 , and its related metal hexacyanates have aroused intensive interest because of their potential application as molecule-based magnets, [21,22] electrochromic materials, [23,24] and potential cation sensors.…”
Section: Introductionmentioning
confidence: 99%
“…One potential application of these well-defined aggregates may be as etch resists for semiconducting substrates, such as GaAs or Si, and they offer potential access to magnetic or semiconducting nanoscopic patterns on various substrates. [132] Möller, Winnik, and Manners and co-workers have studied cylindrical micelles derived from the self-assembly of PFS-b-poly(dimethylsiloxane) (PFS-b-PDMS, 28b, R=R′ = Me) in the PDMS-selective solvent hexanes which possess an organometallic PFS core and a PDMS corona. Dip-or spin-coating of the micelles is possible and they can be positioned on the surface of a GaAs resist by capillary forces along grooves, which were previously formed from electron beam etching of the surface.…”
mentioning
confidence: 99%